The Influence of Human Resource Development, Leadership Style, and Competence on the Performance of the Mediating Role of Service Quality: Study on Junior High and Senior High School Teachers at IT Al Utsaimin Bangkinang) - Aryadi, Aryadi; Hidayat, Hidayat; Sudirman, Wahyu Febri Ramadhan (LPPPIPublishing, 2024)
This study aimed to determine the effect of HR Development, Competence, and Leadership Style on Service Quality and teacher performance at SMP and SMA IT AL Utsmani Bangkinang. A questionnaire is used to collect data in this research. The population in this study were all teachers at SMP and SMA IT AL Utsmanai Bangkinang with 81 teachers. The sample of this study used the census method with PLS 3.0 Structural Equation Modeling (SEM) analysis. The results showed that HR development had a positive and insignificant effect on Service Quality. The results showed that HR development had a positive and insignificant effect on Service Quality, Competence had a positive and significant effect on Service Quality, Leadership Style had a positive and significant effect on Service Quality, and Human Resources Development had a positive and significant effect on performance.